2004
DOI: 10.2139/ssrn.510062
|View full text |Cite
|
Sign up to set email alerts
|

Negotiated Shareholder Value: The German Version of an Anglo-American Practice

Abstract: In comparative political economy it has become commonplace to distinguish between two types of corporate governance systems. In shareholder systems, influence over company management is concentrated with institutional investors holding small percentages of companies' shares. In stakeholder systems, influence is shared between large shareholders, employees, the community, and suppliers and customers. This paper contributes to the literature addressing recent changes in the German variant of the stakeholder syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
0
16
0
3
Order By: Relevance
“…For example, many recent studies of Germany have shown that the country has undergone major institutional change; in a sense, German fi rms have experienced an Anglo-Saxonization. Over-all, Germany remains a CME, but the German "model" is now very different from what it was in the past (Beyer / Höpner 2003;Deeg 2005aDeeg , 2005bJackson 2005c;Vitols 2004).…”
Section: Capitalism As Confi Gurations: Domains Dimensions and Typomentioning
confidence: 99%
“…For example, many recent studies of Germany have shown that the country has undergone major institutional change; in a sense, German fi rms have experienced an Anglo-Saxonization. Over-all, Germany remains a CME, but the German "model" is now very different from what it was in the past (Beyer / Höpner 2003;Deeg 2005aDeeg , 2005bJackson 2005c;Vitols 2004).…”
Section: Capitalism As Confi Gurations: Domains Dimensions and Typomentioning
confidence: 99%
“…Here firms benefit from high coordination across different domains, including employment relations, and develop strong capabilities based on their human assets and relational linkages to other firms. However, a literature on hybrid forms of corporate governance suggests that increasing pressures from capital markets may lead stakeholder-oriented firms to take bolder and faster adjustments to changes in technology and product markets (Vitols, 2002(Vitols, , 2004. For example, Aoki (2010) argues that external monitoring of internal linkages of corporate organization may be beneficial in giving corporate insiders important signals about their overall business strategy and help benchmark their efforts against competitors.…”
Section: Voc and Comparative Advantagementioning
confidence: 99%
“…etwa Jürgens/naumann/Rupp 2000;Klages 2006). Auf betrieblicher ebene entstehe allenfalls ein Modell des "verhandelten Shareholder Value" (Vitols 2003), denn die einführung von Shareholder Value-Maßnahmen (wie beispielsweise Aktienoptionsprogrammen) müsse nun in einer um institutionelle Investoren erweiterten Stakeholder-Koalition aus beschäftigten, großaktionären, Zulieferern und Kunden verhandelt werden.…”
Section: Introductionunclassified